Polymorphous Sweat Gland Carcinoma: An Immunohistochemical and Molecular Study - Ronen, Shira; Aguilera-Barrantes, Irene; Giorgadze, Tamara; Šteiner, Petr; Grossmann, Petr; Suster, Saul (The American Journal of dermatopathology, 2018)
Polymorphous sweat gland carcinoma is an uncommon low-grade malignant adnexal tumor with a marked predilection for the distal extremities. Histologically, the lesions are characterized by a cellular proliferation showing a combination of growth patterns, including trabecular, solid, tubular, cribriform, or adenoid cystic and pseudopapillary. The immunohistochemical and molecular profile of these tumors has not yet been properly addressed. We have studied 3 cases of polymorphous sweat gland carcinoma using a broad panel of immunohistochemical markers including cytokeratin AE1/AE3, CK5/6, MOC31, p40, p63, p16, chromogranin, synaptophysin, CD56, MIB-1, estrogen receptor, progesterone receptor, androgen receptor, BER-EP4, smooth muscle actin, epithelial membrane antigen, carcinoembryonic antigen, CD117, S100 protein, HBME-1, DOG1, vimentin, and mammaglobin. We also examined for the MYB-NFIB fusion by fluorescent in situ hybridization (ISH) and for human papilloma virus by ISH. Our studies show that cytokeratin AE1/AE3, CK5/6, p40, p63, p16, chromogranin, and CD56 stains were positive in all 3 cases. All 3 cases were negative for MYB-NFIB fusion by fluorescent ISH which rules out adenoid cystic carcinoma. DNA ISH studies for high-risk human papilloma virus were negative in all cases. MIB-1 proliferation index was very high (30%-70% nuclear positivity), supporting a malignant phenotype. The positivity for chromogranin and CD56 suggests partial neuroendocrine differentiation. The differential diagnosis includes metastases from internal malignancies, basal cell carcinoma, and other benign and malignant adnexal neoplasms such as adenoid cystic carcinoma, ductal eccrine carcinoma, and microcystic carcinoma. Positivity for p16 in combination with chromogranin and CD56 may be potentially good markers for differentiating this tumor from other adnexal tumors.
Keywords: nádory potních žláz; Female; ženské pohlaví; Carcinoma, Skin Appendage; Immunohistochemistry; lidé; imunohistochemie; Male; nádorové biomarkery; Aged; Sweat Gland Neoplasms; Biomarkers, Tumor; hybridizace in situ fluorescenční; lidé středního věku; senioři; mužské pohlaví; In Situ Hybridization, Fluorescence; Middle Aged; karcinom kožních adnex; Humans